2011
DOI: 10.2147/opth.s17751
|View full text |Cite
|
Sign up to set email alerts
|

Transcorneal electrical stimulation improves visual function in eyes with branch retinal artery occlusion

Abstract: Purpose:To investigate the effects of transcorneal electrical stimulation (TES) on eyes that have a branch retinal artery occlusion (BRAO).Subjects and method:We studied two eyes having a BRAO, with an interval between the onset of symptoms and the beginning of treatment of >16 weeks (longstanding cases), and in three eyes with an interval of <16 weeks (fresh cases). The visual functions of the eyes were assessed by the best-corrected visual acuity (BCVA), multifocal electroretinograms (mfERGs), and automated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…In their studies with RAO patients, Inomata et al [13] and Oono et al [15] used stimulation currents ranging from 0.50 to 1.10 mA. These values are, remarkably, comparable to the values used in the present study, despite significant differences in techniques.…”
Section: Discussionsupporting
confidence: 80%
“…In their studies with RAO patients, Inomata et al [13] and Oono et al [15] used stimulation currents ranging from 0.50 to 1.10 mA. These values are, remarkably, comparable to the values used in the present study, despite significant differences in techniques.…”
Section: Discussionsupporting
confidence: 80%
“…TES has been reported to improve visual function in humans with retinal artery occlusion, non-arteritic ischaemic optic neuropathy and traumatic optic neuropathy, 11–13 as well as inherited retinal dystrophies, such as Best vitelliform macular dystrophy. 14 In RP, an initial pilot study assessing six sessions of weekly TES in eight participants showed significant improvements in kinetic perimetry and scotopic ERG function.…”
Section: Introductionmentioning
confidence: 99%
“…All studies were small; some had sham controls. Effective use of TES for eye conditions included nonarteritic ischemic neuropathy, 14 branch retinal vein occlusion, 15 Stargardt’s disease, 16 retinitis pigmentosa, 17 and Best vitelliform retinopathy. 18 Frequency-specific microcurrent (FSM) has been used extensively in the field of physical medicine and rehabilitation for pain relief and accelerating tissue recovery.…”
Section: Introductionmentioning
confidence: 99%